Pengaruh Naungan Pohon terhadap Keanekaragaman Dung Beetle di Blok Pemanfaatan Tahura Wan Abdul Rachman (Effects of Tree Shading on the Dung Beetle Biodiversity in the Utilization Block of Wan Abdul Rachman Great Forest Park) - Novia Dewara; Bainah Sari Dewi; Sugeng Prayitno Harianto (Jurnal Sylva Lestari, 2020)
Bioindicator of the level of destruction of tropical forests and habitats can be seen from the presence of dung beetle. Dung beetle plays an important role in regulating the function of ecosystems. The purpose of this study was to determine the effect of tree shading on the dung beetle diversity in the the Utilization Block of Wan Abdul Rachman Great Forest Park (Tahura WAR). The method used was the trap method. Traps were planted parallel to the soil, then the collected data was analyzed with diversity index (H`), evenness index (E), and abundance index (E). The results found three species of dung beetles, namely Cattarsius mollosus, Onthopagus sp, and Aphodius marginellus. Diversity index of dung beetle in the area with tree shading (H '= 1.09) was greater than without tree shading (H' = 0 ,9). The evennes index (E) and abundance index (R) of dung beetle in the area with tree shading were E = 0.99 and R = 0.66, while without tree shading were E = 0.82 and R = 0.96. Comparison of the diversity of dung beetle in the the area with tree shading and without shading was 21: 8. This means that the dung beetle could maintain a stable population under tree shading. Dung beetle prefers the area with tree shading due to its suitability for the flight activity, suitable habitat condition, and the availability of food sources. The management of Tahura WAR is expected to increase land cover so that the existing ecosystems could remain sustainable. Keywords: biodiversity, dung beetle, Tahura WAR, tree shading